Analisis Kearifan Lokal Pesta Buah dan Bunga di Berastagi dalam Perspektif Komunikasi Budaya - Purba, Endah Rananda Gita Br; Ritonga, Muhammad Husni (eScience Humanity Journal, 2024)
This study aims to determine the analysis of local wisdom of fruit and flower parties in Berastagi in the perspective of cultural communication This research The method used in this study is Qualitative Discriptive, which provides an overview and identification based on qualitative data. Nazir (2003) explains that the descriptive method not only provides an overview but also explains relationships, makes predictions and obtains the meaning and implications of a problem to be resolved. and directly to the field directly. The results of this research are cultural communication at the Karo fruit and flower festival through traditional media and art performances, through art performances during fruit and flower parties, the entire series of events uses traditional Karo dance. This performance features the Landek dance and the famous five-series dance in Tanah Karo. This festival is a clear example of how local traditions and culture can contribute to sustainable development and preservation of cultural heritage. The supporting factor in this fruit and flower festival is the awareness and concern of the Karo community, actively participating in the event. Mutual cooperation and the success of the event, as well as government support, provide a legal and financial basis for cultural promotion through regional tourism programs. The obstacles experienced are changes in lifestyle, the influence of foreign culture and modern lifestyles which can reduce people's interest, especially the younger generation, in local traditions. Because for them, this event has only become a spectacle, not an application and can be an example for preserving culture.